Ancient Maya economics: models, markets, and trade routes - Chase, Arlen F.; Chase, Diane Z.; Chase, Adrian S. Z. (Frontiers in Human Dynamics, 2025)
Research in the Maya area has now generated sufficient archeological data to better define past economic systems. Our traditional understanding of the ancient Maya was largely driven by archeological finds related to the elite stratum of society and by general anthropological theory that was not focused on complex societies. These past theoretical lenses have led to misconceptions about not only ancient Maya social complexity, but also economic and trade systems that can now be better interpreted and summarized over time through a combination of archeological data, epigraphic texts, and social science theory. These data show that the ancient Maya used market systems that moved goods throughout regional landscapes for consumption by elite and non-elite individuals and also incorporated extensive water-borne trade throughout their history.